Lessons from Flipping Subjects in Engineering: Effectiveness of Student Learning in a Flipped Environment at the University Level - Hoult, Ryan; Peel, Murray; Duffield, Colin (Journal of civil engineering education, 2021)
This paper outlines the subjective and quantitative outcomes of the introduction of the flipped classroom approach to two engineering subjects at the University of Melbourne. In this approach, lectures are delivered online as opposed to the traditional method of being provided in person. To facilitate learning, after each part of an online lecture, students completed an activity to reflect upon and review the content via compulsory questionnaires. Students would then attend formal classes in person (e.g., workshops) in which they would participate in interactive and collaborative activities related to the online lecture material. Surveys were provided to the students at the beginning of the semester to understand their perceptions of different learning activities. The surveys indicate that students who did well on the questionnaires also did well in the subject with a positive trend between questionnaire scores and final grades in both subjects. The survey results suggest that the flipped classroom method could provide students with better learning outcomes for subjects at the university level if implemented in a way that promotes active and student-centered learning. Some recommendations are provided based on the results of this paper for the implementation of the flipped classroom method for future subjects at the university level.